2013
DOI: 10.1016/j.yhbeh.2012.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Sex and hormonal influences on seizures and epilepsy

Abstract: Epilepsy is the third most common chronic neurological disorder. Clinical and experimental evidence supports the role of sex and influence of sex hormones on seizures and epilepsy as well as alterations of the endocrine system and levels of sex hormones by epileptiform activity. Conversely, seizures are sensitive to changes in sex hormone levels, which in turn may affect the seizure-induced neuronal damage. The effects of reproductive hormones on neuronal excitability and seizure-induced damage are complex to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(58 citation statements)
references
References 180 publications
1
55
0
2
Order By: Relevance
“…Certain syndromes such as juvenile myoclonic epilepsy, generalized tonic clonic activity on waking, benign rolandic epilepsy, photosensitive epilepsy, reading epilepsy and some generalized epilepsy syndromes present during adolescence (or menarche in girls), when levels of sex hormones rise due to puberty (Grϋnewald et al, 1992;Velišková et al, 2010;Velišková and Desantis, 2013). Indirect influences on epileptic syndromes through effects on sleep also occur with changes in prolactin (Lin et al, 2002).…”
Section: Relationships Between Hormonal States and Seizure Occurrencementioning
confidence: 99%
“…Certain syndromes such as juvenile myoclonic epilepsy, generalized tonic clonic activity on waking, benign rolandic epilepsy, photosensitive epilepsy, reading epilepsy and some generalized epilepsy syndromes present during adolescence (or menarche in girls), when levels of sex hormones rise due to puberty (Grϋnewald et al, 1992;Velišková et al, 2010;Velišková and Desantis, 2013). Indirect influences on epileptic syndromes through effects on sleep also occur with changes in prolactin (Lin et al, 2002).…”
Section: Relationships Between Hormonal States and Seizure Occurrencementioning
confidence: 99%
“…For example, hormonal replacement therapy initiated as estrogen monotherapy in a postmenopausal woman, was shown to be associated with a decrease in seizure incidence (Peebles et al, 2000), and improvement in seizures has been observed following estrogen treatment in patients with absence and tonic–clonic seizures, and also around the ovulation, suggesting that estrogen also may have anticonvulsant effects (Jacono and Robertson, 1987). These apparent disparities are, possible, because estrogen may have dose dependent effects on seizures, as indicated in some experimental data on kainic-acid induced seizures (for a more detailed information, please see the review by Veliskova and Desantis (2013)). Of note is also that seizures can lead to changes in sex hormone levels, for example, it has been reported that temporal lobe seizures, may lead to reduced testosterone levels (Mejias-Aponte et al, 2002; Morris and Vanderkolk, 2005; Verrotti et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical observations and translational research efforts suggest that these features are all influenced to a significant degree by sex (Veliskova and Desantis, 2013)[Perucca, Camfield, et al, in this issue][Scheffer and Gecz, in this issue][Savic and Engel, in this issue][McCarthy and Kight, in this issue][Moshe and Giorgi, in this issue][Galanopoulou and Akman, in this issue][Jones et al, in this issue][vanLuijtelaar et al, in this issue][Scharfman, in this issue][Harden and Koppel, in this issue][Reddy, in this issue][Perucca, Tomson, et al, in this issue][Pitkanen, in this issue]. For example, epidemiological and genetic studies have revealed that some syndromes are more common in females, including those which are thought to be X chromosome-linked (e.g., Aicardi syndrome, Rett syndrome [RS], and protocadherin 19-related infantile epileptic encephalopathy) as well as those that show gender differences due to different genetic and non-genetic factors (e.g., juvenile myoclonic epilepsy).…”
Section: Introductionmentioning
confidence: 99%
“…Other syndromes are more common in males (e.g., Ohtahara syndrome, infantile spasms [IS], Lennox–Gastaut syndrome, Landau–Kleffner syndrome, and febrile seizures), with males exhibiting an overall incidence of seizures and prevalence of epilepsy slightly greater than that of females. Additional studies have demonstrated sex-specific patterns of seizure susceptibility, laterality, and generalization; brain regional dysfunction between ictal periods; and seizure-associated neuronal injury in epileptic disorders, such as temporal lobe epilepsy (TLE) (Veliskova and Desantis, 2013)[Perucca, Camfield, et al, in this issue][Scheffer and Gecz, in this issue][Savic and Engel, in this issue][McCarthy and Kight, in this issue][Moshe and Giorgi, in this issue][Galanopoulou and Akman, in this issue][Jones et al, in this issue][vanLuijtelaar et al, in this issue][Scharfman, in this issue][Harden and Koppel, in this issue][Reddy, in this issue][Perucca, Tomson, et al, in this issue][Pitkanen, in this issue]. There is also emerging evidence that common pathological features in epilepsy syndromes are linked with sex differences, such as subtle distinctions in white matter associated with hippocampal sclerosis that can be identified in patients with TLE with diffusion tensor imaging (Oguz et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation